Вплив низьких та високих концентрацій протипухлинного препарату таксолу на клітини анапластичного раку щитовидної залози - Тронько, М.Д.; Пушкарьов, В.М.; Старенький, Д.В.; Пушкарьов, В.В.; Ковзун, О.І.; Попадюк, І.Д. (Видавничий дім "Академперіодика" НАН України, 2008)
We studied changes of the cell cycle and the mitochondrial membrane potential, as well as the caspase activation in response to antitumour drug Taxol on the ARO cell line of anaplastic thyroid cancer. Taxol activated the cleavage of the caspase substrate starting from a drug concentration of 5 nM. Maximum activation was observed at 25 nM, and the increase in the Taxol concentration to 100 nM resulted in the reduction of caspase activation. Concomitant to caspase activation, we observed the loss of the mitochondrial membrane potential in cells, which indicates the initiation of the mitochondrial apoptotic pathway. At a concentration of 100 nM of Taxol, most cells lost its mitochondrial membrane potential. Low Taxol concentrations (10 nM) caused changes of the cell cycle typical of apoptosis. Higher Taxol doses starting from 50 nM arrested the cell cycle at G2/M phase. Possible types of cell death induced by the treatment with low and high doses of Taxol on thyroid cancer cells are discussed.